Peningkatan kemampuan Literasi Kebudayaan Kewargaan dan sikap multikultur Siswa melalui Model Pembelajaran Creative Problem Solving berbasis LMS - Putu Suardipa; I Nengah Suastika; I Komang Sesara Ariyana (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2022)
The aim of the study was to find out the significant influence of LMS-based Creative Problem Solving learning models on students on the ability of Cultural Literacy of Citizenship and multicultural attitudes.  Experimental research is a non-equivalent post-test only control group design. The population in this study was 197 elementary students in Singaraja City and and the study sample amounted to 60 students with the specifications of students of grade IV Of State Elementary School 1 Banjar Tegal which amounted to 30 students as an experimental class and grade IV Elementary School 1 Great Package which amounted to 30 students as a control class.  Simple random sampling is used as a sample determination for experiments and control groups. The data is analyzed using MANOVA. The results showed: 1) Based on the data of the analysis on hypothesis 1 obtained F values of 11.331, df = 1, and Sig = 0.001, This means that significance smaller than 0.05 can be concluded that there is a significant difference in state cultural literacy between students studying with lms-based Creative Problem Solving Learning Model with conventional learning model;  2) Based on the data of the analysis on hypothesis 1 obtained F values of 22.749, df = 1, and sig = 0.000, This means sig values smaller than 0.05 can be concluded that there is a significant difference in multicultural attitudes between students who follow the LMS-based Creative Problem Solving Learning Model and students who follow conventional learning models, 3) Manova analysis results show that the calculated F price for Pillae Trace, Wilk Lambda, Hotelling's Trace, Roy's Largest Root from the implementation of lms-based Creative Problem Solving Learning Model is smaller than 0.05. Thus, there is an influence on the application of LMS-based Creative Problem Solving Learning Model on state cultural literacy and multicultural attitude simultaneously in students.Keywords: Citizenship Cultural Literacy, Multicultural Attitudes, Creative Problem Solving Learning Model, LMS.